Synthesis of core–shell ZSM-5@meso-SAPO-34 composite and its application in methanol to aromatics. Issue 69 (29th July 2015) - Zhang, Ling; Jiang, Zhong-Xiang; Yu, Yue; Sun, Chong-Shuai; Wang, Yu-Jia; Wang, Hai-Yan
<x xml:space="preserve">Abstract</x> A core/shell-structured ZSM-5@meso-SAPO-34 composite catalyst was hydrothermally synthesized through overgrowing SAPO-34 molecular sieve on the external surface of ZSM-5.